Manuais Didáticos e literatura infantil: as leituras infantis no Brasil e em Portugal - Souza, Renata Junqueira de [UNESP]; Girotto, Cyntia Graziella Guizelim Simões [UNESP]; Simoes, Rita (My University, 2013)
The school textbook is an important pedagogic resource in the classroom, and it is frequently the only one. But, an analysis of the Maternal Language’s textbooks in Brazil and in Portugal allowed us to detect serious didactic obstacles to the learning of the language in its semiotic omnifuncionality. In this paper we are going to present the results of a project that involves the presence of a children’s literature book in the classroom instead of the textbook adaptations. We developed activities before, during and after the reading in a fourth grade class of an Elementary School in Brazil and Portugal having the aim of build readers.

O manual escolar é um importante recurso pedagógico no contexto de sala de aula, sendo frequentemente o único. Todavia, uma análise de livros didáticos de ensino de Língua Materna tanto no Brasil quanto em Portugal permite-nos detectar a existência de importantes obstáculos didáticos a uma efetiva aprendizagem da língua em sua potencialidade humanizadora. Neste texto apresentamos os resultados de um projeto que teve como primeiro objetivo levar para a sala de aula um livro de literatura infantil substituindo as adaptações que abundam nos manuais. Partindo deste livro foram feitas atividades antes, durante e depois da leitura com uma turma de crianças portuguesas e outra de crianças brasileiras 4º ano de escolaridade, tais atividades objetivaram à formação de crianças leitoras.
Text books and children’s literature: children’s reading in Brazil and Portugal